System Dynamics-Based Rice Procurement Strategy to Support Food Stability in Critical Periods - Rizki Alifnur Harmawan; Erna Mulyati; Agus Purnomo (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
Rice procurement strategies play a crucial role in ensuring supply availability and stabilizing prices in traditional markets, particularly during critical periods characterized by higher demand and limited supply. This study aims to implement a rice procurement method in traditional markets in Tangerang Regency, using system dynamics during critical periods. This study uses an AnyLogic-based simulation approach, utilizing secondary data on rice prices, stock availability, and rice demand sourced from the Tangerang Regency Food Information System and the Tangerang Regency Agriculture and Food Security Office. Simulations were conducted in four different scenarios: standard conditions in May 2025, the period after Eid al-Adha in July 2025, the dry season with decreased food distribution in September 2025, and the Christmas and New Year season in December 2025. The results show that the period after Eid al-Adha is the most critical scenario, with the largest stock deficit of 12,146 and the lowest service level of 89.88%. Based on simulation findings and risk assessments, a mixed procurement strategy emerged as the most effective option to ensure stock availability, mitigate the risk of supply deficits, and facilitate future rice price stability during critical times.